Comparative Analysis of Power Quality Indices for Different Lighting Techniogies in Public Lightning - Jurica Perko; Srete Nikolovski; Ljubomir Majdandžić (International Journal of Electrical and Computer Engineering (IJECE), 2018)
As with any other product, having electricity of a certain quality is very important for consumers. Its quality has become the key feature that can be disturbed by loads based on power electronic devices. Electricity producers are striving to provide reliable and quality electricity supply to consumers. Public lighting systems that are based on LED lighting technology can potentially positively or negatively affect the power quality because they contain power electronics components in LED drivers. Because of that, two 7-day measurements were conducted on the same public lighting branch but with different lighting technologies (high pressure sodium, known as HPS and LED technology). Results of the measurements were analysed and compared. By analysing the results, other problems were also identified by using LED lighting technology. These problems are addressed in the conclusion of the paper.